INTERNET OF VEHICLES-BASED REAL-TIME VEHICLE TRACKING - Yeddula, Raghunath Reddy; P, Vetrivelan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The leading-edge vehicle tracking and scanning system based on embedded board is intended and executed to observe any vehicle from differentÂ locations. Every year, many numbers of vehicles are stolen. To prohibit thievery, a phenomenal type of negator is preowned, like padlock, disk breakÂ lock and more which is a defensive motion, but it is not safe for all designs. The main impartial is to initiate a control entity that shows the locale spotÂ of a vehicle proving by global position system (GPS) to find the position. Here, global system for mobile (GSM) is accepting for communicating withÂ the vehicle that easily finding a steal. The entity is built for trying out the mastery of the locale spot that transmits to the user when the motion is inÂ exciting direction and stable in the city and some other areas. This whole entity is built by bringing together a Raspberry Pi with GPS, general packet radio service (GPRS), and GSM. The preferred entity makes better use of unique automation that based on the Raspberry Pi. This entity works on theÂ GPS and GSM SIM 900A modules which consists all the three things for communication. GPS and GPRS circulate the chasing information to the serverÂ to transmit the message to the mobile number which is saved in this sector for communicating through GSM. This preferred entity also acquires theÂ traveler’s protection by testing liquefied petroleum gas effused gas sensor MQ135 and temperature DS18B20 sensor. Â